Digital Era Teacher Followership: The Role of Effective Teachers as Followers in Supporting Principals - Humairoh, Widya Belqis; Adnan Zulkarnaen; Hasyim Asy’ari (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
This study aims to explore the role of teachers as effective followers in supporting principals in the digital era. The research method used is qualitative with a library research approach. Data was obtained from various literature such as books, journal articles, and reports from educational institutions. The results of the study indicate that teachers have a strategic role in supporting principal policies, especially in integrating technology into learning. Effective teachers contribute to improving the quality of learning through the use of technology, supporting the principal's vision and mission, and adapting to the transformation of digital education. The success of the teacher's role is influenced by several supporting factors, such as access to technology, ongoing training, and commitment to digital learning. However, challenges such as limited infrastructure, resistance to change, and high workloads are still obstacles that need to be overcome. As an integral part of digital education, teachers are expected to be able to optimize technology training, strengthen collaboration with principals, and utilize digital media as an effective means of communication. This effort requires synergy between teachers, principals, and other stakeholders to improve the effectiveness of education in the digital era.